Asociación de marcadores sanguíneos en los resultados de embarazo con rotura prematura de membranas, hospital Iquitos “César Garayar García” 2023 - Cahuaza Reategui, Jhoanna Melu Marilia (2025)
Objective: To determine the association between neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios and pregnancy outcomes in cases of premature rupture of membranes among patients treated at the Iquitos “César Garayar García” Hospital during 2023. Methodology: Observational study with an analytical and cross-sectional design. Results: A total of 69.3% of pregnant women presented at least one adverse pregnancy outcome. A significant association was identified between these outcomes and factors such as younger maternal age, preterm delivery, inadequate prenatal care, multiparity, and presence of vaginal discharge syndrome. Additionally, leukocytosis, neutrophilia, and higher neutrophil-to-lymphocyte ratio (NLR) were significantly associated with increased risk of obstetric complications. The NLR showed a cut-off point of 4.45, with a sensitivity of 44.3% and specificity of 80.3% for predicting adverse outcomes. Conclusion: The neutrophil-to-lymphocyte ratio (NLR) is an independent predictor of unfavorable obstetric outcomes, highlighting its potential usefulness as a complementary clinical marker.